Sense of Legal Practice and Settings of Legal Theory: A Comment to R. Dworkin’s Radical “Hermeneutics” - S. N. Kasatkin (Теоретическая и прикладная юриспруденция)
This paper discusses conception of legal interpretativism proposed by a famous American jurist, Ronald Dworkin (1931–2013) in context of problems of “practical orientation” of legal theory. The first part of the paper states key attitudes of R. Dworkin’s interpretive approach as to understanding of law and legal practice, interpretative character of legal propositions, and necessary practical “involvement” of legal theorist. The second part assesses R. Dworkin’s interpretive theory, emphasizes importance of its “practical direction”, as well as its argumentative and hermeneutic potential. Simultaneously, the paper highlights a number of “dark spots” within the American jurist’s conception that require elucidation/justification. These are linked with an unjustified universalization of argumentative character of legal practice and of the idea of “the best moral light”, with lack of clarity in the idea of legal theorist’s “participation” in the practice being comprehended, as well as with radicalism and insufficiency of R. Dworkin’s arguments to neutralize legitimate plurality of legal doctrines.